AIR QUALITY IMPACT ANALYSIS IN BANJARMASIN CITY - Agustina, Norsita; Indah, Meilya Farika; Chandra, Chandra; Handayani, Eka; Fauzan, Akhmad (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
The rapid increase in the vehicle population and the level of household and industrial activity as well as various community activities in the City of Banjarmasin that cause air pollution in the City of Banjarmasin. For this reason, this study aimed to evaluate the level of air pollution that is currently occurring in the city of Banjarmasin. This study measured the level of air pollution at three locations that are sampled for air quality testing, namely Antasari Central Market, Trisakti Port, and Pal 6 Terminal in Banjarmasin City. Measurement of air pollution used mobile laboratory equipment in collaboration with the Banjarmasin City Basic Health Laboratory. This survey measures the quality of Carbon Monoxide (CO), Nitrogen Dioxide (NO2), and Sulfur Dioxide (SO2). The results of the study found that at point 2 which is a location in the Antasari Central Market, Banjarmasin City, it exceeded the quality standard threshold of 3925/µg/Nm3 which has been set by Government Regulation of the Republic of Indonesia (PPRI) Number 41 of 1999 concerning Air Pollution Control. Which explains the quality standard of CO. Air quality (Carbon Monoxide) of 30.000/ g/Nm3. Meanwhile, measurements at Trisakti Port obtained a mild carbon monoxide air quality of 4.25/µg/Nm3. Parameters SO2 (Sulfur Monoxide), the results of field measurements get good results. This study concludes that the air quality in the City of Banjarmasin is good, this is due to the Covid-19 pandemic conditions reducing community activities to work outside except in terms of meeting daily needs.